Respira fácil, hay una aplicación para eso: Uso de tecnologías de la información y la comunicación para evitar la contaminación del aire en Bogotá - Allen Blackman; Bridget Hoffmann (Inter-American Development Bank (IDB), 2022)
– Ambient air pollution is a leading cause of death in developing countries. In theory, using smartphone apps, text messages, and other personal information and communication technologies to disseminate real-time information about such pollution can boost avoidance behavior like wearing face masks and closing windows. Yet evidence on their effectiveness is limited. We conduct a randomized controlled trial to evaluate the impact of training university students in Bogotá, Colombia to use a newly available municipal government smartphone app that displays real-time information on air quality. The training increased participants acquisition of information about air quality, their knowledge about avoidance behavior, and their actual avoidance behavior. It also enhanced their concern about other environmental issues. These effects were moderated by participants characteristics. For example, the training was generally less effective among job holders.
Keywords: Q53; Q56; Q58; I15; 330; contaminación del aire; Colombia; información; ensayo controlado aleatorizado; experimento; aplicación de teléfono inteligente